The history & culture of pakistan (skill book) - Coulson, alan (Peak Publication; Pakistan, 2012)
The History & Culture of Pakistan (Skill Book) offers an interactive approach to understanding Pakistan's rich history, cultural heritage, and societal development through skill-building activities.